TINGKAT PENERAPAN SANITASI DAN HIGIENE PADA PRODUK PERIKANAN SEGAR DI PASAR TRADISIONAL KABUPATEN BANTUL - , INTAN PRATIWI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sanitation The traditional market is one of the final chain from marketing and distribution of fresh fish products to consumers. and hygiene are the main factors to be applied to the marketing of fresh fish that can be consumed safety. The aim of research was to determine the level of implementation sanitation and hygiene on fresh fish products in Traditional Markets that managed by Village Government and Local Government District in Bantul. Study used survey method. Sampling using simple random sampling. Study analyzed with descriptive method. using Based on survey from 15 of traditional market in Bantul District, obtained sanitary conditions that applied by fish merchant, as follows : well water without addition of chlorine, conditions in contact with the surface of the fish is still less attention, merchant still less attention to personal hygiene, sanitation and hand -washing facilities in some markets are not yet available, merchant still less attention to personal hygiene, sanitation and hand washing facilities in some markets not yet available, the most merchant do not apply the cleaning procedure contact with the fish that is go od, distance the water source with sewer line is enough (minimal 10 metre), merchant stored chemicals in a safe place and away from fish, merchant does not attention to their personal healthy, has not been applied pest prevention in the market area. Based on the Level of implementation sanitation and hygiene fish merchant in district market and village market not yet fulfilled standard (not achieve an average total indicator that is 5 = very good). Anyway, the implementation of sanitation and hygiene conditions of the district market is still good if compared with village market. District market has average total indicator 2,46 (less good) whereas village market has average total indicator 2,07 (less good). test results of TPC (Total Plate Count) of the 4 traditional markets in the Bantul district, they were Imogiri market, Pleret market, Bantengan market, and Kepek market known microbial content in red tilapia and shrimp exceeds 5.0 x10 5 cfu / ml and did not fulfilled the requirements of Indonesian National Standard (SNI). Based on t-test results, the sample shrimp and red tilapia in the Pleret market significantly different real, the sample red tilapia in the market Bantengan also significantly different real. It shows that the value of TPC in both markets far exceeds of the TPC standar 5.0 x10 5 cfu/ml (5.7 log cfu/ml). Sample of red tilapia and shrimp that sold in traditional markets of Bantul district does not fulfilled the requirements set by the SNI (Indonesian National Standard).